2019
DOI: 10.1080/10717544.2019.1625467
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional nanoplatform based on star-shaped copolymer for liver cancer targeting therapy

Abstract: With high morbidity and death rates, liver cancer has become one of the most common cancers in the world. But, most chemotherapeutic anticancer drugs have high toxicity as well as low specificity. To improve the treatment modalities and enhance the therapeutic effect of liver cancer, a brand new liver-targeting nanoparticle (NP), Ent-11a-hydroxy-15-oxo-kaur-16-en-19-oic acid (5 F)-loaded cholic acid (CA)-functionalized star-shaped poly (lactic-co-glycolic acid) (PLGA)-polyethylene glycol (PEG)-lactobionic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Finding more appropriate drugs or delivery methods with lower cytotoxicity and fewer side effects are important tasks for HCC chemotherapy. 14,15 Alkaloids are organic compounds containing nitrogen that occur nature, most of which are basic, some of which are neutral (eg, colchicine) or even acidic (eg, theophylline, theobromine). A wide range of pharmacological properties and effects have been reported, such as antimalarial (eg, quinine), antiasthma (eg, ephedrine), anticancer (eg, homoharringtonine), cholinomimetic (eg, galantamine), vasodilatory (eg, vincristine), antiarrhythmic (eg, quinidine), analgesic (eg, morphine), antibacterial (eg, chelerythrine), and antihyperglycemic activities (eg, vincristine and vinblastine).…”
Section: Discussionmentioning
confidence: 99%
“…Finding more appropriate drugs or delivery methods with lower cytotoxicity and fewer side effects are important tasks for HCC chemotherapy. 14,15 Alkaloids are organic compounds containing nitrogen that occur nature, most of which are basic, some of which are neutral (eg, colchicine) or even acidic (eg, theophylline, theobromine). A wide range of pharmacological properties and effects have been reported, such as antimalarial (eg, quinine), antiasthma (eg, ephedrine), anticancer (eg, homoharringtonine), cholinomimetic (eg, galantamine), vasodilatory (eg, vincristine), antiarrhythmic (eg, quinidine), analgesic (eg, morphine), antibacterial (eg, chelerythrine), and antihyperglycemic activities (eg, vincristine and vinblastine).…”
Section: Discussionmentioning
confidence: 99%
“…There are many reports on the encapsulation drugs and/or its models in micelles, 3,23,32,33,40,42,44,62 microspheres, 25,63,64 and nanoparticles 5,43,65,66 formed by star-shaped PLA-PEG molecules. Star-shaped polymers have a smaller hydrodynamic radius and lower solution F I G U R E 7 Structures of H-shaped (5), dumbbell-shaped ( 6) polymers.…”
Section: Drug Deliverymentioning
confidence: 99%
“…Scheme 2). 62 Star-shaped PEG-PLA self-assembled into nanoparticles with a size of 50 nm and critical micellar concentration of 2.10 μg mL −1 and hydrophobic drug (doxorubicin) was efficiently encapsulated into the core of particles. An in vitro study demonstrated that the nanocarrier can ferry doxorubicin selectively into tumor tissue, rapidly enter cancer cells, and release its payload in response to an intracellular reductive environment, resulting in excellent antitumor activity in vitro.…”
Section: In Vitro and In Vivo Investigationsmentioning
confidence: 99%
“…In another report, Gong and colleagues have synthesized CA derived star-shaped poly (lacticco-glycolic acid) (PLGA)-polyethylene glycol (PEG)-lactobionic acid (LA) polymer and fine-tuned the liver targeting potency of their as-synthesized polymeric nanoparticle. [67] Jeong et al have reported the synthesis of lactic acid conjugated polycholate nanoparticle and shown their assembling ability toward Erythropoietin encapsulation. [68] Feng et al reported the CA conjugated tri-armed PEG-based star-like block copolymer via ATRP method.…”
Section: Design Trends Of Cholic Acid-based Polymersmentioning
confidence: 99%